Aktivitas Olahraga Pada Masyarakat Pesisir di Kabupaten Tegal (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
This study aims to determine the general picture of society, sports activities, open space and sporting potential that can be explored in the coastal Tegal. This study was descriptive qualitative research. Location of the study covers 11 villages and one village. The target in this study is the coastal communities and coastal areas Tegal. Examination of the validity of data by source triangulation and triangulation techniques. Analysis of the data by means of data reduction, data display, and conclusion. The study states the majority of coastal communities Tegal are women amounted to 41 279 people with a high school education level, religion Islam, working in agriculture and the majority use the region as rice cultivation with an average air temperature 27,4Âºc. Sports activities in coastal communities Tegal sequentially majority is football, badminton, volleyball, aerobics, table tennis, running and basketball time in the afternoon and held in the village square. Total runag open as many as 24 rooms. with as many as five broad categories cramped space and as many as 19 categories of space. Sporting potential that can be explored in coastal areas Tegal is beach soccer, beach volleyball, badminton, table tennis, and rowing. For that is expected for all elements of the central government Tegal to the village and the community should jointly take care of nature and open spaces, encouraging create sporting culture in the community so that people woke up healthy and develop the potential of the existing sports so that sports development will be better.